IMPLIKASI PERKAWINAN POLIANDRI TERHADAP UPAYA PEMENUHAN HAK ANAK DI KECAMATAN BOTUPINGGE - IYAN KASIM; NIRWAN JUNUS; SRI NANANG MEISKE KAMBA; MUTIA CHERAWATY THALIB; KARLIN Z. MAMU; MUHAMAD KHAIRUN KURNIAWAN KADIR (GANEC SWARA, 2024)
This research aims to find out the implications of polyandrous marriages for efforts to fulfill children's rights in Botupingge District.  This research uses sociological juridical research methods.  Sociological juridical research has as its object the study of community behavior.  The community behavior studied is behavior that arises as a result of interacting with the existing norm system, namely the perpetrators of the practice of polyandrous marriage in the Botupingge sub-district.  The results of this research show that the implications of polyandrous marriages for efforts to fulfill children's rights in the Botupingge sub-district hinder the realization of children's rights, both in terms of providing identity on a child's birth certificate which is only recorded as the mother's child, causing harm to interests,  threatens the fulfillment, protection and enforcement of children's rights both regarding family law and children's psychology